Real Time Shipment Tracking System Using RFID - H, Medhat; Awadalla, A (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
This paper presents a viable system for online shipment tracking using RFID technology. It aims to find the location where exactly it is at an instance of time, from the time of shipment to the time of delivery. The system has a developed web-based database-driven application that facilities its management and provides useful information about the shipment. A complete prototype of the proposed system was implemented and tested to validate the system functionality. The results show that the system is promising for on line shipment tracking.